(untitled) (Journal of Global Arts Studies, 2024)
Background: The mediums and forms of artistic creation are becoming increasingly diverse, enabling artists to more conveniently express their artistic concepts and viewpoints, and facilitating the smooth realization of their works. At the same time, this diversification grants the public the right to freely and equally participate in artistic creation. Objective: To explore the significance of the application of artificial intelligence in digital art and to analyze the ethical and value orientation issues it brings. Methods: The author examines three of their own art projects that integrate digital technology and artificial intelligence, discussing key issues such as digital interaction, multi-sensory experiences, and the role of AI in driving the advent of the singularity from an interdisciplinary perspective. Results: Through the analysis of the three art projects, the study provides topics for further discussion, reveals the potential therapeutic functions of digital art in interaction and immersion, and proposes future directions for the development of AI and digital art. Conclusion: Artists and the public should demystify artificial intelligence, and artists should incorporate the therapeutic functions of digital technology in their creations to achieve the healthy and sustainable development of AI and digital art.